Indoleamine 2,3-dioxygenase mediates inhibition of virus-specific CD8+ T cell proliferation by human mesenchymal stromal cells - Hong, Jian; Hückelhoven-Krauss, Angela; Wang, Lei; Schmitt, Anita; Wuchter, Patrick; Kleist, Christian; Bieback, Karen; Ho, Anthony Dick; Schmitt, Michael (Cytotherapy, 2016)
Background aims - Mesenchymal stromal cells (MSCs) exert broad immunomodulatory functions. We recently demonstrated a strong suppressive effect of MSCs on virus-specific CD8+ T-cell proliferation. Here, we further explored the underlying mechanism. - Methods - The role of indoleamine 2,3-dioxygenase (IDO) in inhibition of virus-specific CD8+ T-cell proliferation by human MSCs was investigated using a mixed lymphocyte peptide culture assay, IDO intracellular staining and IDO inhibition through 1-methyl-DL-tryptophan (1-MT). Moreover, the influence of the number of passages and the seeding density of MSCs on their IDO expression and immunosuppressive ability were investigated. - Results - MSCs with low IDO expression exhibited a reduced suppressive effect on both allo-antigen- and cytomegalovirus (CMV)-specific CD8+ T-cell proliferation. 1-MT could partially abrogate the suppressive effect. MSCs inhibited CMV-specific CD8+ T-cell proliferation regardless of the number of passages and the seeding density. IDO expression of MSCs was not significantly affected by the number of passages or the seeding density. In addition, the interferon (IFN)-γ level in the culture system was crucial for MSCs to inhibit the proliferation of CMV-specific CD8+ T cells. - Summary - MSCs inhibit virus-specific CD8+ T-cell proliferation through IFN-γ-induced IDO activity, resolving current conflicting reports on this issue and indicating the potential need for prophylaxis and surveillance of virus infection in patients treated with MSCs. In addition, our study makes a contribution to the development of MSC potency assay for clinical use.